ʺImproving the content of Engineering and Teaching Education in the context of forming the national system of qualificationsʺ - Nazarkin, O.; Korolova , N. (Problems of Engineer-Pedagogical Education, 2024)
The article is devoted to the study of modern approaches to improving the content of engineering and pedagogical education in the context of reforming the system of vocational education and the development of a national qualification system. It is proved that one of the key problems is the inconsistency of the content and quality of higher education in general (and vocational education in particular) with the actual needs of society and the national economy, the international labor market. The inconsistency of terminology and regulatory documents, in particular, educational and professional standards, the National Qualifications Framework, the classifier of professions and international regulations, also have a negative impact. The structure of the VET system is considered according to the data of the register of educational entities of the EDEBO, according to which the percentage of municipal, state and private educational institutions is determined; the main directions of reforming the system of vocational (vocational-technical) education are identified: effective management and financing, compliance of the content and quality of education with the needs of the labor market; public-private partnership. The content component of the implemented program "EU4Skills: Better Skills for a Modern Ukraine" to support the VET reform. The close mutual connection between the systems of engineering and pedagogical education and vocational education and training has been presented, such as: engineering and pedagogical education affects the quality of training of workers (through graduates) and the effective functioning of the VET system, while it depends on the requirements of the educational process in the VET system and must constantly adjust the training of graduates in accordance with its needs. The analysis of professional and educational standards for specialists of working professions is carried out and the requirements for the development of standards of engineering and pedagogical education have been considered. Ways to improve the national training system have been proposed, considering the strategy of education development in Ukraine. The necessity of creating an integral national qualification system for the integration of activities in the field of awarding, confirming, recognizing qualifications between educational entities and stakeholders has been proved.